2021
DOI: 10.26905/jpp.v6i1.5543
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Peran Stakeholders Dalam Pengembangan Pariwisata (Studi Kasus Pada Kepulauan Banda)

Abstract: Banda Islands, also known as the "Spice Islands", is a group of spice-producing islands located in central Maluku District. The Banda Islands are included in the UNESCO tentative list as the World Heritage Centre with the criteria (iv), (vi), (x). Banda islands are also included in the National Tourism Destination (DPN) Maluku province and one of the National Tourism Development Area of Indonesia (KPPN). Banda Islands as a tourist destination has been known for a long time because of the diversity of attractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Particular stakeholder contributions are made in accordance with their specific roles and domains. Research by Dewi (2013) in Jatiluwih tourism village, Herdiana (2019); Handayani and Warsono (2017) di Karang Jahe Coastal tourism, Kristiana and Nathalia (2019) in Biak Numfor, Suherlan et al (2020) in Gubugklakah tourism village, Salouw (2021) in Banda, showed how the important role of stakeholder and in tourism destination development, preservation and conservation.…”
Section: Community Conservation and Preservation Perspectivementioning
confidence: 99%
“…Particular stakeholder contributions are made in accordance with their specific roles and domains. Research by Dewi (2013) in Jatiluwih tourism village, Herdiana (2019); Handayani and Warsono (2017) di Karang Jahe Coastal tourism, Kristiana and Nathalia (2019) in Biak Numfor, Suherlan et al (2020) in Gubugklakah tourism village, Salouw (2021) in Banda, showed how the important role of stakeholder and in tourism destination development, preservation and conservation.…”
Section: Community Conservation and Preservation Perspectivementioning
confidence: 99%
“…Collaboration in the tourism industry only became formally recognized in the mid-1980s (Bramwell, Bill;Lane, 2000). Various examples of the successful development of tourism with the concept of stakeholder collaboration were written by (Nuryanti & Hwang, 2002), (Carlisle et al, 2013), (Nyanjom et al, 2018), and (Salouw, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Before describing the role of each stakeholder, stakeholder identification is carried out to find out each actor who plays a role in a destination (Salouw, 2021). Based on in-depth interviews with various parties, this study finds that three main sectors collaborate in RAI tourism development (table 1).…”
Section: Stakeholders Identificationmentioning
confidence: 99%
“…Although in the last two years there has been a downward trend in world tourism due to the Covid-19 pandemic [2], [3], the Government of Indonesia, through the ministry of tourism, continues to make various policies to revive Indonesian tourism [4]. As part of the Indonesian state, Maluku Province has an important role in Indonesian tourism because of the potential for natural tourist attractions and the island's tourist attractions [5]. Maluku Province tourism is known for its archipelagic tourism potential [5], which is unique due to its isolation and limitations [6].…”
Section: Introductionmentioning
confidence: 99%
“…As part of the Indonesian state, Maluku Province has an important role in Indonesian tourism because of the potential for natural tourist attractions and the island's tourist attractions [5]. Maluku Province tourism is known for its archipelagic tourism potential [5], which is unique due to its isolation and limitations [6]. The phenomenal growth of the tourism industry parallels the current development of the internet and social media [7], [8].…”
Section: Introductionmentioning
confidence: 99%